PENGARUH MEDIA PICKER WHEEL UNTUK MENINGKATKAN LITERASI MEMBACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV SD NEGERI 90 PALEMBANG - putri dinanti; Hetilaniar; Dina Sri Nindiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of implementing Picker Wheel learning media to improve students' reading literacy in Indonesian language subjects of grade IV of state elementary school 90 Palembang. This study is an experimental study in the form of Quasi Experimental Design, with Nonequivalent Control Group Design. The population in this study was all grade IV of state elementary school 90 Palembang. The determination of the sample used a purposive sampling technique, so that there were 2 classes, namely IV.C as an experimental class consisting of 28 students and IV.B as a control class consisting of 28 students. The data collection techniques used by researchers in this study were observation and interview techniques, tests, and documentation. For the test technique, multiple choice questions were given to determine the reading literacy of students at the beginning and after being given treatment. And finally, the documentation technique was used to obtain photos of activities during the research process. The data analysis technique in this study used parametric statistical tests in the form of normality tests, homogeneity tests, and Independent Sample T-Tests. The results of the normality test, obtained pretest and posttest value data were normally distributed. Furthermore, through hypothesis testing using the Independent Sample T-Test test, it was obtained t_count = 5.787 and t_table = 2.004 and a significant value of 2 tailed of 0.000. Thus, the results of the T test show that 5.787> 2.004 and a significant value of 0.000 <0.05, then H_0 is rejected and H_a is accepted. Thus, there is an influence of the Picker Wheel learning media to improve students' reading literacy in the Indonesian Language subject of grade IV of SD Negeri 90 Palembang.